The influence of crop rotations, fertilizer and pesticide application on soil microbial diversity, community composition, and wheat yield - Ainash Nauanova; Aldabergen Kiyas; Sayagul Kenzhegulova; Roza Sarmanova; Nazymgul Shumenova; Dana Yerpasheva (Cogent Food & Agriculture, 2025)
This study investigated the impact of crop rotation and fertilizer/pesticide application on soil fertility, microbial diversity, and wheat yield. The experiment was conducted at the A.I. Barayev Scientific-Production Center, Akmola Region, Kazakhstan, using five treatment variants: continuous wheat without inputs (2), continuous wheat with inputs (2b), wheat-after-pea with inputs (25e), wheat-after-oats with inputs (39), and wheat-after-fallow with inputs (39b). Agrochemical analysis revealed significant differences in nitrogen, phosphorus, potassium, and organic matter content across treatments, with fertilizer application increasing nutrient levels in certain variants. Microbial diversity was assessed using 16S rRNA gene sequencing, revealing distinct microbial communities dominated by Actinobacteriota in continuous wheat without inputs and Proteobacteria in fertilized treatments. Wheat yield data showed a significant increase in 2024 in the rotation system with wheat following pea, despite no significant differences in microbial diversity. The results suggest that microbial diversity is influenced by nutrient availability and that the use of fertilizers and crop rotation practices impacts both soil chemistry and microbial community composition.